2016
DOI: 10.4314/ijbcs.v10i3.41
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation saisonnière des eaux de puits à usage maraîchère et domestique de Korhogo (Côte d’Ivoire)

Abstract: Cette étude a été conduite afin de déterminer les caractéristiques physico-chimiques et microbiologiques des eaux de puits à usages domestiques et agricoles du département de Korhogo. Les paramètres physico-chimiques et microbiologiques ont été analysés suivants les techniques décrites par AFNOR. 18 puits ont été échantillonnés durant les saisons pluvieuse et sèche. Les résultats des analyses physico-chimiques montrent que les eaux sont légèrement acides et faiblement minéralisées avec des valeurs de conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
1
4
1
3
Order By: Relevance
“…In Senegal, a study carried out near the edge of Tanna Lake in the Niayes gives a contamination rate of 35% of the wells (Dieng, 2008). The contamination rate of 76.92% of the samples from wells in this study area is much higher than those found in the studies cited above, lower than the rate of 88.88% of Korhogo market garden and domestic water wells in Ivory Coast (Yapo et al, 2016). The widespread contamination by pesticides can be explained by two facts: the two sample collections seasons take place during the months of September, which corresponds to a period rainy and crops continue to receive further treatments with pesticides.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In Senegal, a study carried out near the edge of Tanna Lake in the Niayes gives a contamination rate of 35% of the wells (Dieng, 2008). The contamination rate of 76.92% of the samples from wells in this study area is much higher than those found in the studies cited above, lower than the rate of 88.88% of Korhogo market garden and domestic water wells in Ivory Coast (Yapo et al, 2016). The widespread contamination by pesticides can be explained by two facts: the two sample collections seasons take place during the months of September, which corresponds to a period rainy and crops continue to receive further treatments with pesticides.…”
Section: Discussioncontrasting
confidence: 66%
“…These four organochlorine pesticides were found in the waters of the Nakamba dam in Burkina Faso (Ouattara et al, 2012) and other authors in West Africa (Soclo, 2003;Mawussi, 2008;Agagbé, 2008;Agbohessi et al, 2012;Ngom et al, 2012). Deltamethrin has been quantified in well water in Korhogo (Yapo et al, 2016), in Niayes (Ngom et al, 2012). Already the study conducted in the cotton producing area in 2007 detected the residues of eight pesticides in well water at low volumes (Dem et al, 2007), then the work of Maiga et al, (2014) resulted in quantifications of organochlorine pesticides in well waters to finish with the results of this study which found high levels of organochlorine pesticides with deltamethrin.…”
Section: Discussionmentioning
confidence: 99%
“…La zone se caractérise par une végétation constituée de savane arborée et arbustive, un climat de type soudanais. La géologie de la zone n'est pas favorable à la présence de grands aquifères et les seules réserves importantes d'eaux souterraines se situent dans les fissurations du granite, ou dans les colluvions de marigot de moindre importance (Yapo et al, 2016). Les températures moyennes journalières s'élèvent à 29 °C environ en saison sèche et à 25 °C en saison des pluies.…”
Section: Materiel Et Methodes Zone D'étudeunclassified
“…Approximately 1/3 of vendors declared to use spontaneous fermentation practices depending on environmental conditions. During the dry season, the warm room temperature (~29˚C) [32] sustained the spontaneous fermentation and delivered FDP in about 17-19 h. In the rainy season, the room temperature was relatively low (under 25˚C) [32] and fermentation took much longer, so the milk was initiated via backslopping or through the addition of an industrial yogurt as described above.…”
Section: Plos Onementioning
confidence: 99%